Michael Scriven and "The Missing Half of Quantitative Evaluation" - Brian Yates; Nadini Persaud (The Evaluation Center at Western Michigan University, 2024)
Although Michael Scriven is one of the most recognized parents of program evaluation in general, it may be surprising to learn that he also was a founder of cost-inclusive evaluation (CIE) in particular. CIE incorporates into evaluations information on the amounts, types, and monetary values of resources used by programs to achieve outcomes, and, increasingly, the monetary value of those outcomes (Herman et al., 2009; Persaud & Yates, 2023; Yates, 1996). Michael Scriven blazed a trail toward routine use of cost, cost-effectiveness, and cost-benefit analyses by emphasizing that evaluations should measure costs as well as nonmonetary and monetary outcomes, and should compare costs and outcomes for alternative programs in cost-effectiveness and cost-benefit analyses. Scriven also was emphatic that CIE be recognized as a core evaluator competency. Noting that "cost analysis" in evaluation was "the missing half of quantitative evaluation" (Scriven, 2008a, p. iii), he did not immediately succeed in convincing most evaluators that program costs, and monetary program outcomes, were essential to assess. However, his publications, his supervision, and his encouragement of junior colleagues legitimized and recognized CIE as nothing else could.